Inhibition of PKC disrupts addiction-related memory - Howell, Kristin K.; Monk, Bradley R.; Carmack, Stephanie A.; Mrowczynski, Oliver D.; Clark, Robert E.; Anagnostaras, Stephan G. (Frontiers in Behavioral Neuroscience, 2014)
The atypical PKC isoforms, PKMζ and PKCλ have been proposed as integral substrates of long-term memory. Inhibition of these isoforms has recently been demonstrated to be sufficient for impairing the expression and maintenance of long-term potentiation. Additionally, the pseudosubstrate inhibitor, zeta inhibitory peptide (ZIP), which effectively blocks PKMζ and PKCλ, has previously been shown to disrupt associative memory; very little is known about its effects on pathological nonassociative forms of memory related to addiction. The neural and molecular substrates of memory and addiction have recently been argued to overlap. Here, we used ZIP to disrupt PKMζ and PKCλ activity to examine their role in cocaine sensitization, a nonassociative, addiction-related memory argued to underlie the transition from casual to pathological drug use. We examined the effects of both continuous and acute administration of ZIP. Even a single application of ZIP blocked the development of sensitization; sustained inhibition using osmotic pumps produced an almost complete blockade of sensitization. Further, a single application of ZIP was shown to reduce membrane-bound AMPAR expression. These results demonstrate a novel, critical role for the atypical PKC isoforms in nonassociative memory and cocaine addiction.